Relation Between Ergosterol and Various Mycotoxins in Different Cheeses - Çetin Kadakal; Nizam Mustafa Nizamoğlu; Tolga Kağan Tepe; Sevda Arısoy; Begüm Tepe; Suat Batu (Turkish Journal of Agriculture: Food Science and Technology)
Thirteen different mostly consumed cheese samples were obtained from different provinces in Turkey and were investigated in terms of contents of ergosterol, patulin and Ochratoxin A (OTA). Ergosterol, patulin and OTA analyses were carried out by using the apparatus of high-performance liquid chromatography (HPLC). Ergosterol contents of samples ranged from 30.27±0.69 to 144.76±9.41 mg/kg. The values of OTA in the samples were ranged from 6.96±0.05 to 41±0.2 µg/kg. Ergosterol was significantly correlated with OTA (r = 0.99, R2 = 0.98). According to this high correlation, ergosterol might be used as a more readily measurable indicator of potential OTA production. No patulin was detected in all samples. Absence of patulin on cheese samples may be explained with unsuitable media for patulin producing.